Relationship of Marriage Age with Pregnancy Acceptance Readiness in Pregnant Mothers in the Work Area of Sumberjambe Public Health Center, Jember Regency - Dwiningtyas, Wilujeng; Azza, Awatiful; Indriyani, Diyan (D'Nursing and Health Journal (DNHJ), 2022)
Introduction: Marriage can be interpreted as a married couple of men and women so commonly referred to as husband and wife. A person is said to be legally married in terms of the age of the two spouses. Law number 16 of 2019 concerning the minimum age limit for marriage for both men and women is the same as the minimum age limit for men, namely 19 years. Couples who are married <19 years are said to be early marriage Method: This study uses quantitative research with a cross-sectional approach. The population in this study were primigravida mothers with a total sample of 92 respondents. Using a simple random sampling technique. The collected data were analyzed by chi-square test. Results: in this study, the results of the analysis of the chi-square test with the results of p-value .000 (<0.005) said that there was a relationship between the age of marriage and the readiness of pregnant women. Conclusion: The age of marriage is closely related to the mother's readiness for pregnancy physically, psychologically, financially, and culturally. Married young teenage girls are still a phenomenon now, there needs to be a role from health workers in providing education in the form of information.